IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (SCHOOL BASED MANAGEMENT) DALAM MEWUJUDKAN SEKOLAH EFEKTIF (STUDI KASUS DI MTS NU SABILUL MUTTAQIN JEPANG MEJOBO KUDUS) - Hadziq, Abdulloh (Pascasarjana IAIN Kudus, 2016)
School is an institution that is expected to realize the qualified human resources; an educational institution which is able to produce qualified graduates will be highly affected by the madrasa effectiveness. The indicators of an effective school are: (1) student learning service, (2) student management and services, (3) school facilities and infrastructure, (4) program and financing, (5) community participation, and (6) school culture. The effectiveness of the school is also very determined by the extent of the institution is able to set the rules or professional management, professional management that is commonly used in improving the quality of schools is the school-based management approach. Madrasa as religious institutions are demanded to do a good management in many ways, one of them is MTs NU Sabilul Muttaqin Mejobo Kudus. The approach in this study is a qualitative approach study using observation, interview and documentation. The result in this study is that school-based management in this madrasa is good and able to realize an effective madrasa.